Partially protonated polyamine resin for efficient separation of copper from nickel electrolyte and preparation method thereof
Through the technology of partially protonated polyamine resin, the problems of precipitation, poor selectivity, low adsorption and desorption waste in the process of copper removal in nickel electrolyte are solved, and the efficient and selective Cu2+ separation and low waste desorption process is achieved. .
Patent Information
- Application Number
- CN202310486452.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The existing chelating resins have precipitation phenomena in the process of removing copper in nickel electrolytes, poor selectivity, low adsorption amount, and the need for high concentration of acid and alkali during the desorption process, resulting in liquid waste.
A partially protonated polyamine resin is used to react chlorine spheres with the polyamine under specific conditions to form a resin with high affinity to Cu2+ but basically not adsorb to Ni2+, and precipitation is avoided by protonation treatment.
The efficient separation of Cu2+ in nickel electrolyte is achieved, which shows high selectivity, and avoids fixed bed precipitation. The acid concentration used during the desorption process is low, reducing liquid waste.
Smart Images

Figure CN116333306B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of wet metallurgy and is a partially protonated polyamine resin used for efficiently separating copper from nickel electrolyte and a preparation method thereof. Background Art
[0002] Nickel is an important metal material for national economic construction. Compared with low-purity nickel, high-purity nickel has excellent corrosion resistance, machinability, electromagnetic properties, etc. and is widely used in chemical industry, marine equipment, nuclear energy, battery and other industries. In the process of producing nickel metal from nickel sulfide concentrate, impurities such as iron, copper, cobalt, lead, zinc, etc. are inevitably present. As a similar element to nickel, copper has a much higher standard potential (+0.337V) than nickel (-0.25V), and is easily precipitated at the cathode first. The general copper removal method can only reduce the concentration to 3mg / L. The impurity Cu in the anode liquid of high-purity nickel is 1.37V. 2+ The concentration needs to be reduced to below 0.3 mg / L. Conventional methods often fail to meet the copper removal standards for high-purity nickel.
[0003] Compared with other copper removal methods, the chelating resin method has attracted much attention due to a series of advantages such as good adsorption selectivity, high removal depth, recyclability, and little influence by alkaline (earth) metal ions.
[0004] The following are the main studies on the application of chelating resin in removing copper from nickel electrolyte. Liu Fuqiang [Jiangsu Province, CN102643990[P].2016] et al. invented a method for removing trace copper from high-purity nickel using chelating resin. After treatment, the purity of nickel can be increased by one to two orders of magnitude without introducing impurities or causing pollution. The method has significant economic benefits and broad application prospects. Qiu Xiaoqing et al. from Central South University [Chem. Pap. 2018, 72, 2071–2085; J. Disper. Sci. Technol. 2018, 1561299; Hydrometallurgy, 2018, 180, 121-131; Trans. Nonferrous Met. Soc. China, 2018, 28, 2553-2565] studied a series of chelating resins: PS-AMP: Cu adsorption capacity was 1.53 mmol / g, Ni adsorption capacity was 0.50 mmol / g, and the selectivity coefficient was 643; PS-AMPY: Cu adsorption capacity was 1.22 mmol / g, Ni adsorption capacity was 0.44 mmol / g, and the separation coefficient was 2242; CP-AMPO: Cu adsorption capacity was 0.8921 mmol / g, Ni adsorption capacity was 0.0496 mmol / g, and the selectivity coefficient was 2000. Experiments show that this type of chelating resin has achieved good results in simulated electrolytes. Si-AMPY-1 resin was prepared, with a Cu adsorption capacity of 0.5806mmol / g and a Ni adsorption capacity of 0.0582mmol / g. As the copper-nickel concentration ratio increased from 1:1 to 1:5000, the selectivity coefficient increased from 0.35 to 3238.26. The results show great potential for deep copper removal from nickel electrolytes. In these studies, the importance of the selectivity coefficient of chelating resins in the use of nickel electrolytes for copper removal was emphasized.
[0005] However, there are still some problems in the application of chelating resin in the process of removing copper from nickel electrolyte: for example, free amine chelating resin will produce precipitation during the fixed bed adsorption process [Hydrometallurgy, 2010, 104, 14-19]; polyamine resins containing other heteroatoms such as O, S, and P often have Cu 2+ 、Ni 2+ The phenomenon of poor selectivity [J.Iran.Chem.Soc.2017,14(12):2557-2566]; grafting common short-chain polyamines, such as diethylenetriamine, often has poor selectivity for Cu 2+The adsorption capacity is low [Ion Exchange and Adsorption, 2013, 29(2), 108-116]; aminomethylpyridine type chelating resins commonly used in hydrometallurgy, such as Dowex M4195 produced by Dow Chemical and CuWRAM produced by Purity Systems Inc, are all protonated to avoid fixed bed precipitation. The adsorption process mainly replaces H + However, during the desorption process, a high concentration of acid and alkali is required to achieve complete desorption, resulting in a waste of desorption liquid. Summary of the invention
[0006] In view of the above problems, the present invention provides a protonated polyamine chelating resin for efficiently separating copper from nickel electrolyte. The chelating resin of the present invention is effective in removing copper from nickel electrolyte. 2+ Has high affinity but is weak to Ni 2+ It has almost no adsorption, shows high selectivity, and is not easy to cause fixed bed precipitation.
[0007] In order to achieve the purpose of the present invention, the technical solution adopted is: a partially protonated polyamine resin for efficient separation of copper from nickel electrolyte, the functional group of which is as shown in Formula 1:
[0008]
[0009] The structure of polyamine resin is as shown in Formula 2:
[0010]
[0011] In the formula, the substrate is chlorine ball (chloromethylated polystyrene resin), the dotted frame is the functional group, n is the number of -CH2CH2NH- repeating units, and the value range of n is 1-9.
[0012] The protonated polyamine resin is prepared by washing the resin shown in Formula 2 to a strong acid state and then washing it with deionized water to a neutral state.
[0013] The present invention also provides a method for preparing the partially protonated polyamine resin for efficiently separating copper from nickel electrolyte, comprising the following steps:
[0014] Chlorine balls and polyamines in a solvent at a molar ratio of 1:3 to 1:20 are fully reacted at 60 to 100°С to obtain a polyamine resin, which is filtered and washed, then acid-washed to pH = 1 to complete protonation, and then washed with water until the effluent is neutral to obtain a partially protonated polyamine resin.
[0015] Further, a chlorine ball having a chlorine content of 3 to 5 mmol / g is weighed.
[0016] Furthermore, the reaction time is 12 to 24 hours.
[0017] Furthermore, after filtering, the mixture was washed with deionized water three times, ethanol three times, and water three times.
[0018] Furthermore, protonation was performed using 1 mol / L HCl (a relatively low acid concentration that can achieve both 2+ desorption, so that the resin can be recycled).
[0019] Compared with the prior art, the present invention has achieved the following beneficial effects: the polyamine resin of the present invention has a significant effect on the removal of copper from nickel electrolyte. 2+ Has high affinity but is weak to Ni 2+ It has almost no adsorption, shows high selectivity, and is not easy to cause fixed bed precipitation. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 :PS-PEI + The Cu under different initial pH conditions 2+ 、Ni 2+ Adsorption amount.
[0021] Figure 2 :(a)PS-PEI + , (b) PS-PEI + Adsorption of Cu 2+ and (c) PS-PEI + Adsorption of Ni 2+ N1s spectrum.
[0022] Figure 3 :PS-PEI + Dynamic adsorption (left) and desorption (right) diagram of .
[0023] Figure 4 : Dynamic adsorption diagram of preparation of high-purity nickel anolyte. DETAILED DESCRIPTION
[0024] The present invention will now be further described in conjunction with specific embodiments. The following embodiments are intended to illustrate the present invention rather than to further limit the present invention.
[0025] The selectivity of the resin can be expressed by the selectivity coefficient α Cu / Ni To express it, the calculation formula is as follows:
[0026]
[0027] Where: C e represents the concentration of metal ions in the solution when adsorption reaches equilibrium, Q e It indicates the amount of metal ions adsorbed per gram of dry resin at adsorption equilibrium. Cu / Ni The larger the value, the better the resin is at Cu 2+ The better the selectivity.
[0028] The synthesized PS-PEI + Resin for Cu 2+ 、Ni 2+ In the study of adsorption, the formula for calculating the adsorption amount is:
[0029]
[0030] Where q is the adsorption capacity of the resin for metal ions (mmol / g); C0 and C1 are the initial concentration and concentration of metal ions after adsorption in the solution (mmol / L), V is the volume of the adsorption solution (L), and m is the dry weight of the resin (g).
[0031] The calculation formulas for the saturated adsorption and desorption amounts during the dynamic adsorption process are as follows:
[0032]
[0033] dm d =M×CVdV (3-4)
[0034] In the formula, q a is the saturated adsorption capacity (mmol / g), m d is the desorption amount (mg), C0 is the initial metal ion concentration of the dynamic adsorption solution (mmol / L), C V is the metal ion concentration in the effluent collected by dynamic adsorption and desorption (mmol / L), V is the volume of the effluent (L), M is the molar mass of the metal ion (g / mol), and m is the dry weight of the resin (g).
[0035] Example 1
[0036] (1) Weigh 1 g of chlorine ball with a chlorine content of 3.58 mmol / L, add diethylenetriamine (n=2, with a molar ratio of 1:20) to the chlorine ball, use 10 mL of toluene as solvent, the reaction temperature is 80°C, the reaction time is 12 h, filter, wash with deionized water 3 times, ethanol 3 times, and 1 mol / L HCl 3 times until the effluent is strongly acidic, and then wash with deionized water until the effluent is neutral to obtain protonated PS-DETA + Take half of the resin and then add 1 mol / L NaOH to wash until the effluent is strongly alkaline, then wash with water until neutral to obtain PS-DETA, and dry the two resins in vacuum at 60°C.
[0037] (2) Weigh 1 g of chlorine ball with a chlorine content of 4.5 mmol / L, add triethylenetetramine with n=3 and a molar ratio of 1:10 to the chlorine ball, use 5 mL of toluene as solvent, the reaction temperature is 90° C., the reaction time is 12 h, and after the reaction is completed, wash and dry according to the method of (1) to obtain PS-TETA+ and PS-TETA.
[0038] (3) Weigh 1 g of chlorine balls with a chlorine content of 4.5 mmol / L, add pentaethylenehexamine (PEHA) with n=5 and a molar ratio of 1:20 to the chlorine balls, use 5 mL of toluene as solvent, the reaction temperature is 80°С, the reaction time is 12 h, and after the reaction is completed, wash and dry according to the method of (1) to obtain PS-PEHA + (4) Preferred solution: weigh 1 g of chlorine balls with a chlorine content of 4.5 mmol / g, the molar ratio of chlorine balls to polyethyleneimine with n=9 is 1:20, 5 mL of toluene is used as solvent, the reaction temperature is 100°С, the reaction time is 24 h, and after the reaction is completed, wash and dry according to the method of (1) to obtain PS-PEI + and PS-PEI.
[0039] Example 2
[0040] Prepare a simulated electrolyte solution (Cu 2+ The concentration is 10mmol / L and Ni 2+ The concentration was 1200mmol / L), the amount of resin used was 0.05g, and the selectivity of resins of different polyamine types before and after protonation was compared when the adsorption was saturated.
[0041] In Ni 2+ It is Cu 2+ Comparison of Cu ions before and after protonation of different types of polyamine resins at a concentration of 120 times 2+ The adsorption capacity of PS-PEI was the highest, and it was found that all of them could achieve selective removal of copper under high nickel concentration conditions. + The selectivity of PS-PEI is the highest. 2+ The adsorption amount of PS-PEI + 2 times of that of partially protonated PS-PEI + Almost no Ni adsorption 2+ , from α Cu / Ni The value of PS-PEI + The selectivity of PS-PEI is nearly 10 times higher than that of PS-PEI. + In general, PS-PEI + The selectivity is greatly improved while avoiding the precipitation phenomenon of the fixed bed. + Adsorption studies were performed.
[0042] Table 1 Selectivity coefficients of resins of different polyamine types before and after protonation
[0043]
[0044] Example 3
[0045] Investigating PS-PEI + Cu under different pH conditions 2+ 、Ni 2+ The adsorption performance of single CuSO4 and NiSO4 solutions with different pH values and concentrations of 10mmol / L were transferred to conical flasks, and 0.05g of PS-PEI was added. + Resin, measured adsorption capacity.
[0046] The results showed that (see Figure 1 ), PS-PEI + At pH>3, Cu 2+ The adsorption capacity of PS-PEI is relatively high, reaching up to 1.5mmol / g. + To you 2+ The adsorption effect is better when it is above 4, and the maximum adsorption is about 0.6mmol / g. + Cu 2+ The adsorption amount of Ni is always higher than that of Ni in the range of pH>3. 2+ Common free amine resins will increase the pH of the adsorption solution, which is not conducive to adsorption [Hydrometallurgy, 2010, 104, 14-19; Ion Exchange and Adsorption, 2013, 29 (2), 108-116]. + The adsorption experiment was carried out within the initial pH range of the experiment. The pH of the solution after adsorption was kept below 4. The higher the initial pH, the easier it was to exchange H + , so it has the function of regulating the pH of the electrolyte.
[0047] Example 4
[0048] PS-PEI + In a single Cu 2+ 、Ni 2+ After the solution was saturated with adsorption, the sample was washed with deionized water and dried for X-ray photoelectron spectroscopy (XPS, Figure 2 ) analysis. It was found that PS-PEI + The N1s of PS-PEI can be fitted with two characteristic peaks, namely free amine (399.52 eV, 42.38%) and proton amine (401.74 eV, 57.62%). + After protonation, half of the free amines are protonated, while the adsorption of a single Cu 2+ The subsequent N1s fitting of free amine (399.86 eV, 53.62%) and protonated amine (401.74 eV, 44.05%) indicated that free amine and Cu2+ After binding, the characteristic peak shifted, but the proton amine did not bind to Cu 2+ The change in the proportion of the two types of amines and the decrease in the pH value of the solution all indicate that Cu 2+ On the one hand, it can react with free amines, and on the other hand, it can partially replace the H + , thus reacting with proton amine, thus ensuring that the nickel electrolyte does not produce (Cu(OH)2) precipitation. 2+ After that, the N1s fitting of free amine (399.64 eV, 41.64%) and protonated amine (401.79 eV, 58.36%), adsorbed Ni 2+ The characteristic peak position and area of the nitrogen atom do not change, indicating that Ni 2+ PS-PEI + There is no obvious interaction between them.
[0049] Example 5
[0050] Prepare a simulated electrolyte with a pH of 4 (CuSO4 concentration of 2-10 mmol / g and NiSO4 concentration of 1200 mmol / L), the volume of dry resin used is 3-7 mL, and the flow rate is 5-25 mL / h. When eluting, use 1 mol / L HCl at a flow rate of 5 mL / h.
[0051] In Cu 2+ The concentration is 2~10mmol / g, Ni 2+ In the simulated nickel electrolyte with a concentration of 1200mmol / L, the volume of the dry resin used is 3-7mL, and the flow rate is 5-25mL / h. The nickel electrolyte that meets the requirements of high-purity nickel can be obtained. The copper-nickel adsorption data in the dynamic adsorption data of sequence number (2) is as follows: Figure 3 As shown, it can be seen that Cu 2+ At 179.5 mL, the leakage was 2+ Rapid leakage. The pH of the effluent was measured and maintained at about 3.8 before leakage, and gradually decreased to close to 3 after leakage. At the same time, the dynamic column resin after adsorption saturation was desorbed using 1 mol / L HCl. The amount of desorption was basically the same as the amount of adsorption, indicating that 1 mol / L HCl can be used for good elution. Therefore, the PS-PEI prepared by the present invention + The prepared materials are easier to desorb. The highest Cu 2+ The concentration is about 227.8385mmol / L, while Ni 2+ The highest concentration was 0.03686 mmol / L, and the molar ratio of Cu / Ni in the eluent was 2367, showing high selectivity.
[0052] Table 2 Data of dynamic adsorption example
[0053]
[0054] Note: The concentration of 0.3 mg / L required for high-purity nickel is taken as the breakthrough concentration, and the volume of the effluent before this concentration is recorded as the breakthrough volume. V / C0=0.95 before the outflow is taken as the saturation volume. 2+ The adsorption amount was taken as the saturated adsorption capacity.
[0055] Example 6
[0056] Nickel electrolyte (Cu 2+ Concentration = 0.04mmol / L, Ni 2+ =1400mmol / L concentration) for deep copper removal, the resin dosage is 5mL, the flow rate is 15mL / h, the adsorption curve is as follows Figure 4 As shown:
[0057] Figure 4 Only 1200mL was processed, and there was no leakage, because according to theoretical calculations, 5mL of dry resin can deeply purify about 55L of nickel electrolyte, which is 11,000 times the resin itself, and the treatment efficiency is relatively high. At the same time, the effluent was basically undetectable for copper ions using atomic absorption spectrophotometry, indicating that the depth of treatment is also relatively high. In addition, Figure 4 The pH of the effluent is basically the same as that of the original solution. Figure 3 Keep the pH stable before leakage. + It can deeply remove copper without changing the pH of the solution, and has high application potential in the preparation of high-purity nickel.
[0058] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An application of a partially protonated polyamine resin, characterized in that: Used for separation of copper and nickel in nickel electrolyte; The partially protonated polyamine resin has polyethylene polyamine as a functional group. The synthesis steps of the partially protonated polyamine resin include: fully reacting chlorine balls with a molar ratio of 1:3 to 1:20 with polyethyleneimine with a polymerization degree of 9 at 60 to 100° C. in a solvent to obtain a polyamine resin, filtering and washing, then acid washing to pH = 1 to complete protonation, and then washing with water until the effluent is neutral to obtain a partially protonated polyamine resin.
2. The use of the partially protonated polyamine resin according to claim 1, characterized in that: The chlorine content in the chlorine ball is 3~5 mmol / g.
3. The use of the partially protonated polyamine resin according to claim 1, characterized in that: The reaction time is 12~24 h.
4. The use of the partially protonated polyamine resin according to claim 1, characterized in that: After filtration, the sample was washed with deionized water three times, ethanol three times, and water three times.
5. The use of the partially protonated polyamine resin according to claim 1, characterized in that: 1 mol / L HCl was used for protonation.
Citation Information
Patent Citations
Method for removing trace Cu in high-purity Ni by chelate resin
CN102643990A
Preparation and applications of low-substituted dendrimer adsorption material loaded on crosslinked polystyrene
CN101857652A
Synthetic resin, and preparation method and application thereof
CN102875717A